Látky s estrogenním účinkem ve vodách - Kujalová, Hana; Sýkora, Vladimír; Pitter, Pavel (Chemické listy, 2007)
A broad spectrum of substances showing estrogenic activities in aquatic and terrestrial organisms occur in wastewaters. An overwhelming majority of the compounds are insofar biologically stable that their removal by water treatment is incomplete and thus they contaminate the environment. Chronic expositions to estrogens cause reproduction disorders and evolution defects in a number of animals. With humans, it is assumed that inadequate actions of estrogens in organisms can lead to lower fertility and a higher occurrence of evolution abnormalities. Due to the adverse effects of estrogens, the problems of their occurrence, transport and biotransformation are very topical. The review gives substances of estrogenic nature including their chemical structure, origin, occurrence and interactions with organisms. It brings the usual concentration ranges of most important estrogens in waste and surface waters and documents their poor removability in wastewater purifying plants. Their estrogenic potentials are compared and their biodegradability is evaluated.
Keywords: Biodegradation, Environmental; estrogeny; Estrogens; biodegradace; odpadní vody; chemické látky znečišťující vodu; fytoestrogeny; Water Pollutants, Chemical; Sewage; Phytoestrogens